Distinguishing the players of the digital field - Tim Bergström (Eludamos)
This article explores the field of contemporary gaming practices and preferences among players of various social backgrounds. From a Bourdieusian perspective based on the notion of different capital forms (economic, social, and cultural), the socialisation process of Swedish players of digital games (n=1019) is investigated through a multiple correspondence analysis on questionnaire data. The findings show that the contemporary Swedish gaming culture is clearly divided by gender and age, but not as visibly by social class, birthplace, or upbringing. The article concludes that the contemporary gaming culture restricts present dispositions and future trajectories among the agents of the gaming field.